A common plasma lipidomics signature of cardiometabolic and coronary risk in statin users. (10th June 2022) - Rocchiccioli, S; Di Giorgi, N; Michelucci, E; Signore, G; Scholte, AJHA; Knuuti, J; Buechel, RR; Teresinska, A; Pizzi, MN; Roque, A; Poddighe, R; Parodi, O; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Commission in the H2020 program: Project SMARTool, "Simulation Modeling of coronary ARTery disease: a tool for clinical decision support—SMARTool" Background and aims: The coexistence of elevated plasma triglycerides (TG) and low high-density lipoprotein cholesterol (HDL-C) may contribute to the residual cardiometabolic risk of coronary artery disease (CAD) independently of total cholesterol and low-density lipoprotein cholesterol (LDL-C) absolute plasma levels [1]. Aim of this study is to assess whether a high TG/HDL-C ratio is characterized by a specific lipidomics signature in statin users and its relationship with the coronary risk score defined by coronary computed tomography angiography (CTA). Methods: TG/HDL-C ratio was calculated in 132 patients (68.8±7.7 years, 85 males) with suspected or known CAD referred to coronary CTA and receiving statins treatment in the last 6.3 ± 1.4 years before enrolment. Patients were grouped according to TG/HDL-C ratio quartiles: IQ (≤1.694), IIQ (1.695-2.399), IIIQ (2.400-3.281), and IVQ (>3.282). Coronary CTA exams were analysed according to the modified 17-segment American Heart Association classification [2] and interpretable segments were visually assessed for degree of stenosis and plaque composition. A comprehensive coronary risk score (CTA score) [3], previously validated as predictor of adverse outcome, was calculated in each patient. Except for subjects with normal arteries (CTA score = 0), all patients were classified into 3 groups of CTA score severity:  low (score < 5), intermediate (score 5-20) and high (score > 20) risk [4]. Patient-specific plasma targeted lipidomics was performed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). This approach allowed to quantify 69 circulating lipids encompassing six lipid classes (triacylglycerol [TG], phosphatidylcholine [PC], phosphatidylethanolamine [PE], ceramide [Cer], sphingomyelin [SM], cholesterol ester [CE]). Differential analysis was performed using TG/HDL-C and CTA score annotation. Results: 18 altered lipid species in the group with higher TG/HDL-C ratio were also altered in the group with higher CTA risk score. This common set of lipids is composed of CE(16:0), CE(18:0), PC(38:2), 8 SM [SM(34:2), SM(38:2), SM(41:2), SM(41:1), SM(42:4), SM(42:3), SM(42:1), SM(43:3)], TG(52:1) and 6 PE [PE(34:0), PE(34:1), PE(34:2), PE(36:1), PE(36:2), PE(36:3)], and represents the lipidomics signature associating elevated plasma TG/HDL-C ratio with high CTA risk score in statin users. Conclusion: In patients with stable CAD under statin treatment, a specific pattern of altered lipids, characterized by reduced plasma levels of cholesterol esters and sphingomyelins and increased levels of triacylglicerols and phosphatidylethanolamines, is associated with high TG/HDL-C ratio and high CTA score. This specific lipidomic signature identifies patients with higher residual cardiometabolic and coronary risk, not tackled by current lipid lowering therapy, unveiling possible new molecular targets of treatment.